The next steps for chemo-optimization in lung cancer treatment - Li Feng; Jiang Boao; Fan Xianze; Jiang Ziyan; He Jianxing; Liang Wenhua (Visualized Cancer Medicine)
Chemotherapy has long been the backbone of lung cancer treatment, especially for advanced stages. However, with the rapid development of targeted immunotherapies, traditional chemotherapy faces re-evaluation due to its toxicity and long-term immunosuppressive effects. In the era of immunotherapy, we propose several strategies to optimize chemotherapy use. First, reducing chemotherapy dosage and duration not only sensitizes tumors to immunotherapy but also minimizes the immunosuppressive effects of prolonged chemotherapy, thereby maximizing immune efficacy. Additionally, combining immunotherapy with targeted therapies, anti-angiogenic drugs, dual immunotherapy, or local treatments can substitute chemotherapy’s antiproliferative effects, induce immunogenic cell death, reduce immunosuppressive cells, and improve the tumor microenvironment, enhancing immunotherapy while reducing chemotherapy’s systemic toxicity. We also explore the application of the “Chemo-Holiday” approach in integrating chemotherapy with immunotherapy. The core of this approach is phased, on-demand chemotherapy. Initially, short-term chemotherapy combined with immunotherapy and anti-angiogenic agents achieves rapid tumor control and antigen release, enhancing immune recognition and cytotoxicity. During the maintenance phase, immunotherapy and anti-angiogenic agents take priority to reduce cumulative chemotherapy toxicity. If disease progression occurs, first-line chemotherapy can be reintroduced based on clinical need. In summary, lung cancer treatment is gradually shifting from the traditional “Chemo-on” model to a “Chemo-less” or even “Chemo-free” approach. By reducing chemotherapy frequency and dosage and incorporating novel drugs and technologies to fill efficacy gaps, this strategy enables personalized, less toxic, and more effective treatment options.